2010
DOI: 10.1097/mpa.0b013e3181bdfc76
|View full text |Cite
|
Sign up to set email alerts
|

For Patients Undergoing Pancreatoduodenectomy, Epidural Anesthesia and Analgesia Improves Pain But Increases Rates of Intensive Care Unit Admissions and Alterations in Analgesics

Abstract: For patients undergoing PD, EAA was not associated with clinical benefits except for a modest reduction in postoperative pain, which was limited to a single day. Therefore, in this study, the clinical benefits of EAA seem underwhelming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 21 publications
4
52
0
Order By: Relevance
“…All epidural and IV PCA patients received concurrent IV paracetamol (acetaminophen) 1 g 6-hourly unless contraindicated and standard postoperative care as described in other cohorts. 17 Analysis groups were similar to those reported by Pratt et al 14 : epidural analgesia, IV PCA, functional epidurals, aborted epidurals. Analgesic efficacy was assessed between functional (working) and aborted epidurals at 24 hours, 48 hours, and overall for the duration of pain assessment, which was 2 days.…”
Section: Methodssupporting
confidence: 68%
See 3 more Smart Citations
“…All epidural and IV PCA patients received concurrent IV paracetamol (acetaminophen) 1 g 6-hourly unless contraindicated and standard postoperative care as described in other cohorts. 17 Analysis groups were similar to those reported by Pratt et al 14 : epidural analgesia, IV PCA, functional epidurals, aborted epidurals. Analgesic efficacy was assessed between functional (working) and aborted epidurals at 24 hours, 48 hours, and overall for the duration of pain assessment, which was 2 days.…”
Section: Methodssupporting
confidence: 68%
“…14, 16,17 Inadequate block was the commonest reason for epidural abortion; 70.9% is higher than the 43.1% 14 previously quoted, but definitions vary between studies for epidural blockade, breakthrough pain, and epidural adjustment. 17 Hypotension was the reason for premature abortion in our cohort in only 6.5%, which is lower than the 33% to 41% previously reported, although heterogeneous definitions and practice are caveats that might explain this apparent disparity. 14,16 Our baseline patient demographics were similar to most other cohorts, with slightly more male patients aged 60 to 70 years.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Interestingly, this observation reflects the general opinion throughout the surgical literature. Epidural analgesia provides superior pain relief after PD than IV PCA; 44 however, the impact of epidural analgesia on postoperative morbidity and mortality is not completely understood. Recent studies have suggested that epidural use results in fewer postoperative complications; 45 in contrast, epidural analgesia has been found to promote hemodynamic instability following PD and possibly contributes to an increased incidence of various gastrointestinal and respiratory complications.…”
mentioning
confidence: 99%